‘Nesting networks’: women's experiences of social network support in high-risk pregnancy - Hinton, L; Dumelow, C; Hodgkinson, J; Montgomery, C; Martin, A; Allen, C; Tucker, K; Green, ME; Wilson, H; McManus, RJ; Chappell, LC; Band, R (Elsevier, 2023)
Objective Social support, an individual's social relationships (both online and offline), may provide protection against adverse mental health outcomes, such as anxiety and depression, which are high in women who have been hospitalised with high-risk pregnancy. This study explored the social support available to women at higher risk of preeclampsia during pregnancy by examining personal social networks. Design Semi-structured interviews were accompanied by social network mapping using the web-based social networking tool GENIE. Setting England. Participants Twenty-one women were recruited, of whom 18 were interviewed both during pregnancy and postnatally between April 2019 and April 2020. Nineteen women completed maps pre-natally, 17 women completed maps pre-natally and post-natally. Women were taking part in the BUMP study, a randomised clinical trial that included 2441 pregnant individuals at higher risk of preeclampsia and recruited at a mean of 20 weeks’ gestation from 15 hospital maternity units in England between November 2018 and October 2019. Results Women's social networks tightened during pregnancy. The inner network changed most dramatically postnatally with women reporting fewer network members. Interviews revealed networks were primarily ‘real-life’ rather than online social networks, with members providing emotional, informational, and practical support. Women with a high-risk pregnancy valued the relationships they developed with health professionals during pregnancy, and would like their midwife to have a more central role in their networks by providing informational and, where needed, emotional support. The social network mapping data supported the qualitative accounts of changing networks across high-risk pregnancy. Conclusion Women with a high-risk pregnancy seek to build “nesting networks” to support them through pregnancy into motherhood. Different types of support are sought from trusted sources. Midwives can play a key role. Practice Implications As well as highlighting other potential needs during pregnancy and the ways in which they can be met, support from midwives has a key role. Through talking to women early in their pregnancy, signposting information and explaining ways to contact health professionals regarding informational or emotional support would fill a gap that currently is met by other aspects of their network.